PERSEPSI MASYARAKAT TERHADAP KINERJA DEWAN KEHORMATAN PENYELENGGARA PEMILU: Studi Kasus Persepsi Masyarakat DKI Jakarta Terhadap Kinerja Dewan Kehormatan Penyelenggara Pemilu Pada Pilkada DKI Jakarta Tahun 2017 - Avif Muhammad Fauzhi (2023)
The 1945 Constitution of the Republic of Indonesia in article 22E paragraph (2) states that "General elections are held to elect members of the People's Representative Council, Regional Representative Council, President and Vice President, and Regional People's Representative Council. the issue of the Pilkada was colored by many major events throughout 2017, one of which was the DKI Jakarta Pilkada which took place with two rounds of elections. This research will use research data collection techniques with questionnaires or questionnaires. Then, in questionnaire/questionnaire/survey research, it is necessary to have a population sample from a predetermined research location, namely DKI Jakarta. In analyzing the results of the questionnaire, the authors used quantitative data analysis techniques. Based on the results of calculating the empirical mean and hypothetical mean, the results obtained were that the hypothetical mean (MH) 72 was smaller than the empirical mean (ME) 83.46. So it can be concluded that the perception of the people of DKI Jakarta towards the performance of the Ethics Council of Election Organizers in the 2017 Pilkada has a moderate level of perception. This research aims to describe the perception of the people of DKI Jakarta towards the performance of DKPP in the 2017 DKI Jakarta Pilkada. With regard to aspects of the perception of the people of DKI Jakarta, they are in the moderate aspect.